Drama-based instruction in EFL classrooms: Pedagogical practices in secondary and tertiary education - Dian Pratiwi (Politeknik Negeri Jember, 2026)
Drama-based instruction is widely recognized as an effective approach in English as a Foreign Language (EFL) learning, particularly in enhancing communicative competence and learner engagement. However, its implementation in secondary and tertiary education remains inconsistent, and existing studies are often fragmented and context-specific. This study aims to synthesize recent literature on the roles, impacts, and challenges of drama-based learning in secondary and tertiary EFL classrooms. Using a qualitative library research design, this study analyzed 15 peer-reviewed journal articles and conference proceedings published between 2020 and 2025 through thematic content analysis. The findings indicate that drama-based instruction supports language development, especially in improving speaking fluency, pronunciation, and communicative competence, while also enhancing learner motivation, confidence, creativity, and collaboration. Nevertheless, challenges such as limited instructional time, large class sizes, insufficient teacher training, and students’ reluctance to perform persist. The study highlights the pedagogical value of drama-based instruction and calls for greater institutional support, teacher professional development, and flexible curriculum design to optimize its implementation in EFL classrooms.